2006
DOI: 10.1051/lait:2006008
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the gelation properties of whey protein concentrate and whey protein isolate

Abstract: -The present paper describes a comparative study of the gelation properties of whey protein concentrate (WPC) and whey protein isolate (WPI). Penetration measurements as well as rheological studies revealed that the strength of heat-induced gels prepared with WPI was higher than with WPC. In addition, gels with WPI were clearly more elastic than WPC gels. The storage modulus of WPI and the storage and loss moduli of WPC increased with increasing frequency, while the loss modulus of WPI revealed no clear depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 34 publications
6
26
0
1
Order By: Relevance
“…An exception was found in the case of the defatted gel at pH=4, with a significant decrease in the elastic and viscous modulus (Table 3) when the protein mass fraction was increased. The results for G' and G'' are in the same range of magnitude of the values found in other works for gels produced with bovine WPC (39)(40)(41). However, they are lower than the values found for caprine WPC (39,42) or ovine WPC (39,43) gels.…”
Section: Rheological Properties Of the Thermal Gelssupporting
confidence: 83%
“…An exception was found in the case of the defatted gel at pH=4, with a significant decrease in the elastic and viscous modulus (Table 3) when the protein mass fraction was increased. The results for G' and G'' are in the same range of magnitude of the values found in other works for gels produced with bovine WPC (39)(40)(41). However, they are lower than the values found for caprine WPC (39,42) or ovine WPC (39,43) gels.…”
Section: Rheological Properties Of the Thermal Gelssupporting
confidence: 83%
“…WPI films showed lower DE values than WPC ones, and these differences were significant (p < 0.05). In addition, WPC films exhibited higher values of b than WPI ones (data not shown); this fact was consistent with the slightly yellowish color observed in WPC films, which may be attributed to presence of contaminants e especially fat and phospholipids (Lorenzen & Schrader, 2006). For practical uses, however, such a minor defect of WPC films can be overcome via addition of coloring agents, as frequently done in food packaging films, or else by lamination with opaque outer layers (Hong & Krochta, 2006).…”
Section: Colorsupporting
confidence: 77%
“…Heat induced aggregation and gelation of WPC is known to be influenced by a variety of factors such as ions, heat treatment and pH (Lorenzen & Schrader, 2006;O'Kennedy & Mounsey, 2009;Schmitt, Bovay, Rouvet, Shojaei-Rami, & Kolodziejczyk, 2007). The most pronounced effect of pH in this study was found when changing from pH 6.0 to pH 6.8 (Fig.…”
Section: Heat Induced Gelationmentioning
confidence: 54%
“…However, a contribution from alpha-lactalbumin to the network formation has been reported only to take place when B-LG is present (Gezimati, Creamer, & Singh, 1997). The presence of other substances like fat, lactose and phospholipids is also observed to influence the gelation capacity of whey proteins, as whey protein isolate (WPI) makes stronger gels than WPC from a similar source of whey (Lorenzen & Schrader, 2006). The total amount of -SH groups available influences the gelling time as well as the clarity or the opacity of the formed gels in the way that an increased total -SH gives increased opacity and faster gelation (Hillier, Lyster, & Cheeseman, 1980).…”
Section: Whey Proteins and Gel Network Formationmentioning
confidence: 99%
See 1 more Smart Citation